(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Descriptive geometry is an important discipline in education, which helps to develop spatial thinking, visual perception and analytical skills. However, many students face difficulties in understanding and applying geometric principles and tools. In this article, we will look at various approaches and strategies that can be used to improve students’ skills in the study of descriptive geometry.